Elevated Plasma Levels of Cell‐Free DNA During Liver Transplantation Are Associated With Activation of Coagulation. Issue 12 (4th December 2018) - von Meijenfeldt, Fien A.; Burlage, Laura C.; Bos, Sarah; Adelmeijer, Jelle; Porte, Robert J.; Lisman, Ton
Abstract : Patients undergoing liver transplantation have complex changes in their hemostatic system, and the net effect of these changes appears to be a "rebalanced" hemostatic profile. Recently, a process called NETosis in which a neutrophil expels DNA and proteins that form a weblike structure, has been described as a mechanism of pathogen entrapment. Increasing evidence suggests a pivotal role for neutrophil extracellular traps (NETs) and their main component, cell‐free DNA (cfDNA), in activation of coagulation. Because liver transplantation is associated with substantial (hepatocyte) cell death and intrahepatic neutrophil accumulation, NETs might play an important role in the hemostatic balance during liver transplantation. Here, we determined markers for NETs in the plasma of patients undergoing a liver transplantation and examined their association with activation of coagulation. Markers for NETs and markers for activation of coagulation were determined in serial plasma samples taken from patients undergoing a liver transplantation (n = 21) and compared with plasma levels in healthy controls. We found perioperative increases of markers for NETs with levels of cfDNA and nucleosomes that peaked after reperfusion and myeloperoxidase (MPO)–DNA complexes that peaked during the anhepatic phase. CfDNA and nucleosome levels, but not MPO‐DNA levels, correlated with prothrombin fragment 1+2 and thrombin‐antithrombin complex levels, which are established markers for activation of coagulation. Neutrophils undergoing NETosis were observed by immunostainings in postreperfusion biopsies. In conclusion, although NETosis occurs during liver transplantation, the majority of circulating DNA appears to be derived from cell death within the graft. The perioperative increases in cfDNA and nucleosomes might contribute to the complex hemostatic rebalance during liver transplantation.